Islamic Archaeology in Kota Rantang: A Historical Study of the Existence of the Aru Kingdom in the Development of Islam in North Sumatra - Rosnaubah Harahap; Suprayitno Suprayitno; Nursukma Suri; Rahimah Rahimah (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
Kota Rantang, located in North Sumatra, is rich in Islamic history and cultural heritage in Indonesia. This study aims to explore the existence of Islamic archaeological remains in Kota Rantang and their implications for understanding Indonesian history and culture. The research questions focus on identifying the types of Islamic archaeological remains in this area and how these artifacts provide insight into the development of Islam in Indonesia. The methodology employs a historical approach combined with archaeological techniques, collecting data from sites such as tomb complexes, mosque ruins, and everyday artifacts like statue fragments, jewelry, and pottery. The findings indicate that these remains are crucial for uncovering the past lives of the community and the role of Islam in shaping local cultural identity. In conclusion, the archaeological remains in Kota Rantang not only enrich our understanding of Islamic history in Indonesia but also strengthen the nation's cultural identity.